The politics of disenchantment: Marcel Gauchet and the French struggle with secularization. Issue 1 (2nd January 2017) - Peden, Knox
ABSTRACT: This article looks at Marcel Gauchet's major metahistorical statement, The Disenchantment of the World: A Political History of Religion (1985), and uses it to advance a series of claims about the place of secularization in debates within and about French politics, especially in relation to modern French history. The argument is put forward that Gauchet's work is best understood as offering an alternative philosophy of history to Marxism that could serve to support a broadly republican realignment of French politics in the 1980s. Revisionist historiography concerning the French Revolution likewise played a role in this development, and served as a prerequisite of sorts to Gauchet's broader historical project. The article also considers Gauchet's work in light of postmodern skepticism of the utility of historical metanarratives.